2020
DOI: 10.2478/johh-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Are coastal deserts necessarily dew deserts? An example from the Tabernas Desert

Abstract: Vapor condensation, whether due to dew or fog, may add a stable and important source of water to deserts. This was also extensively assessed in the Negev, regarded as a dew desert. Dew deserts necessitate a large reservoir of vapor, and are therefore confined to near oceans or seas. Yet, examples of such deserts are scarce. Here we try to assess whether the Tabernas Desert in SE Spain can be regarded as a dew desert, and may therefore facilitate the growth of certain organisms that otherwise would not survive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…Only once RH >95% was recorded (95.5% during July 11 th , 2007). Similar findings were also found for the rainless months of June, July, August, and September of 2003-2012 in the Tabernas, during which RH >95% occurred on average for only 0.9-1.1 days a month (Kidron and Lázaro, 2020). These values imply that dew formation is relatively infrequent.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Only once RH >95% was recorded (95.5% during July 11 th , 2007). Similar findings were also found for the rainless months of June, July, August, and September of 2003-2012 in the Tabernas, during which RH >95% occurred on average for only 0.9-1.1 days a month (Kidron and Lázaro, 2020). These values imply that dew formation is relatively infrequent.…”
Section: Resultssupporting
confidence: 83%
“…Dew formation was frequently reported as taking place in the Tabernas and its vicinity (Moro et al, 2007;Uclés et al, 2013Uclés et al, , 2016. Although, as recently substantiated, the occurrence of dew in the Tabernas is actually infrequent as compared to the Negev Desert and therefore the Tabernas cannot be considered a dew desert (Kidron and Lázaro, 2020), many reports concluded that dew formation may play an important role as a water provider for this ecosystem. It was therefore assumed that dew will facilitate the survival and growth of many organisms, such as crustose soil lichens (Moro et al, 2007;Pintado et al, 2010), and will facilitate organism survival also during the harsh dry season (Uclés et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that atmospheric vapor during the winter is lower than during the summer (Evenari et al, 1971) point to the central role played by the TIVF. Also, the relatively low amounts of NRW of ≤0.04 mm (Kidron & Kronenfeld, 2020a, 2020bKidron & Lázaro, 2020) that reach the soil surface from the atmosphere even during heavy dewy days in comparison to the high amounts (up to 0.20-0.30 mm) recorded during the winter, further support the conclusion regarding the central role played by distillation and that TIVF may serve as a principal causative factor for the WDCs. This is supported by the limiting wetting capability of the dewfall reported also from other ecosystems (Fischer et al, 2012;Lázaro et al, 2008).…”
Section: Resultssupporting
confidence: 55%
“…Also, in most cases, capillarity was not excluded. With the Negev regarded as dew desert (Kidron & Lázaro, 2020), pinpointing at the specific causative factor may be more complicated. However, we can rely on numerous dew data that were thoroughly analyzed in the Negev (see review by Kidron & Starinsky, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar semi-arid steppe ecosystem in Spain, the mean number of days per year with suitable conditions for dew formation was 285 d (Uclés et al, 2014). However, this finding is based on measurements with micro-lysimeters consisting of PVC sampling cups with < 0.1 m length, for which it has been shown that they tend to overestimate dew when compared with alternative sampling approaches (Kidron and Lázaro, 2020;Kidron and Kronenfeld, 2020a, b). Our observation that especially nights are prone to the formation of NRW is also documented in the literature.…”
Section: Non-rainfall Water Frequency Duration and Amountsmentioning
confidence: 99%